2007
DOI: 10.1155/2007/84656
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Fate Analysis Revisited: Interpretation of Individual Clone Dynamics in the Light of a New Paradigm of Stem Cell Organization

Abstract: Many experimental findings on heterogeneity, flexibility, and plasticity of tissue stem cells are currently challenging stem cell concepts that assume a cell intrinsically predefined, unidirectional differentiation program. In contrast to these classical concepts, nonhierarchical self-organizing systems provide an elegant and comprehensive alternative to explain the experimental data. Here we present the application of such a self-organizing concept to quantitatively describe the hematopoietic stem cell system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…This approach has also been applied to BMSCs (Coleman et al 2007). Because stem cell behavior is not the result of a cell-autonomous program, but is instead the consequence of complex cell-cell and cell-environmental interactions, a suitable growth environment is essential for achieving the desired differentiated phenotype (Roeder et al 2007). Previous reports have revealed that BMSCs can undergo differentiation into urothelium-like cells.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has also been applied to BMSCs (Coleman et al 2007). Because stem cell behavior is not the result of a cell-autonomous program, but is instead the consequence of complex cell-cell and cell-environmental interactions, a suitable growth environment is essential for achieving the desired differentiated phenotype (Roeder et al 2007). Previous reports have revealed that BMSCs can undergo differentiation into urothelium-like cells.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a simulation study, we previously estimated the magnitude of this effect in a homeostatic reference system, predicting a reduction to one-tenth of the initial clone numbers within the lifespan of a B6 mouse. 26 Although the process of clonal selection is predicted to be enhanced by differences in the growth characteristics of individual cells, 26 the estimated within-strain heterogeneity of clonal properties does not cause a significant acceleration of this process (data not shown). Nevertheless, our model predicts the exhaustion of clones with competitive disadvantages.…”
Section: Predicting the Evolution Of Clonal Compositionmentioning
confidence: 95%
“…23,24 This model has previously been validated in different murine systems 22,25,26 and was valuable for the understanding of disease dynamics and treatment effects in human chronic myeloid leukemia. 27,28 The model features a stochastic single-cellbased approach to analyze stem-cell dynamics on the population as well as on the single-cell level.…”
Section: Introductionmentioning
confidence: 99%
“…Applying such technologies to stem cell cultures will allow us to parse out intercellular communication networks established by the stem cells and their derivatives. Regarding characterization, systems biology approaches to studying interactions between stem cells and their niches, along with in silico modeling, have generated relevant network models capable of predicting whether a stem cell will self-renew or differentiate (29,87,88). These models can provide mechanistic insight into how stem cell-culture heterogeneity influences culture output, can be used to optimize culture output, and can predict how dysregulation may occur in malignancies (29,89).…”
Section: Ecm Microarraysmentioning
confidence: 99%